2012
DOI: 10.1016/j.eururo.2012.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node–Positive Bladder Cancer Treated With Radical Cystectomy and Lymphadenectomy: Effect of the Level of Node Positivity

Abstract: Background The extent of lymphadenectomy needed to optimize oncologic outcomes after radical cystectomy (RC) for patients with regionally advanced bladder cancer (BCa) is unclear. Objective Evaluate the effect of the location of lymph node metastasis on recurrence-free survival (RFS) and cancer-specific survival (CSS) for patients undergoing RC with a mapping pelvic lymph node dissection (PLND). Design, setting, and participants A study of 591 patients undergoing RC with mapping PLND was completed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 18 publications
7
74
1
1
Order By: Relevance
“…Current imaging techniques lack adequate sensitivity and specificity, especially in low-volume metastatic disease. Moreover, it has been shown that in patients with presumably organ confined disease; micrometastatic disease was detected using RT-PCR studies in up to one third of patients with histologically negative lymph nodes 25,26 . Similarly, patients with colorectal, ovarian and urothelial cancers with local relapse, port site seeding and early metastasis after laparoscopic surgery have been previously reported 21,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Current imaging techniques lack adequate sensitivity and specificity, especially in low-volume metastatic disease. Moreover, it has been shown that in patients with presumably organ confined disease; micrometastatic disease was detected using RT-PCR studies in up to one third of patients with histologically negative lymph nodes 25,26 . Similarly, patients with colorectal, ovarian and urothelial cancers with local relapse, port site seeding and early metastasis after laparoscopic surgery have been previously reported 21,27 .…”
Section: Discussionmentioning
confidence: 99%
“…1), 541 and 715 articles were excluded in the careful primary and further screening. Next, we retrieved the full text of remaining 119 articles and finally selected 17 studies that conformed to the eligible criterion [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The baseline characteristics of the 17 studies are described in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…The benefits of more extended PLND's have been previously studied in patients treated with radical cystectomy. A more comprehensive PLND, both in pN0 and pN+ patients, has been shown to be associated with improved clinical outcomes in bladder cancer patients treated with radical cystectomy [17][18][19][20][21][22][23]. It has been suggested that at least in the setting of bladder cancer, extended PLND can lead to cure in some patients with metastasis or micrometastasis to limited node [17].…”
Section: Discussionmentioning
confidence: 97%